Uji Viabilitas dan Vigor Benih beberapa Varietas Padi (Oryza sativa) Setelah Melewati Batas Masa Edar - Tri Rahayuningsih; Firman Aziz Bagus Ariyanto (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Seeds that have exceeded their shelf life generally experience a decline in physiological quality, particularly in terms of viability and vigor. This study aims to determine the viability and vigor levels of several rice (Oryza sativa L.) varieties of Foundation Seeds (Benih Pokok/BP) after surpassing their shelf life. The tested varieties included Inpari 16, Inpari 42, Inpari 45, Sunggal, Memberamo, and Ciherang, obtained from Wonoketro Village, Jetis Subdistrict, Ponorogo Regency. The study was conducted through standard laboratory testing for germination rate and vigor. Results showed a decrease in germination capacity across all varieties, with varying degrees of decline. Inpari 45 showed a germination rate of 39%, Memberamo 33.67%, Sunggal 26.33%, and Ciherang 15.67%, compared to the initial value of 92%. These differences indicate that each variety responds differently to aging and storage conditions. The findings serve as a basis for decision-making regarding the use of expired seeds and are important for seed management in the field.